mHealth low carbohydrate dietary intervention ameliorates glycaemic profile, blood pressure and weight status in people with type 2 diabetes - Despina Kolivas; Liz Fraser; Ronald Schweitzer; Peter Brukner; George Moschonis (npj Metabolic Health and Disease)
Abstract Low carbohydrate diets (LCD) have shown efficacy in managing clinical outcomes in type 2 diabetes (T2D). Incorporating digital tools into health care provides an adjunct treatment modality, to educate patients and provide clinical support. This study examines the effect of a mobile health (mHealth) LCD application (app) on glycaemic profile, blood pressure and weight status, in people with T2D. The study is an online single-arm, pre-post study that recruited people with T2D from around Australia, referred via registered supporting general practitioners (GPs). The intervention (Defeat Diabetes app) provides education and resources on the use of a LCD for ongoing management of T2D. After 3 months, our cohort of 99 participants (mean age 59 ± 11 years, 55 females) showed reduced dietary carbohydrate intake as a proportion of overall energy (−14%kJ/day, 95% CI: −17 to −11). Improvement in the primary outcome HbA1c (−1.0%, 95% CI: −1.3 to −0.7), was associated with reduction in dietary carbohydrate intake. Systolic blood pressure (SBP) improved (−6 mmHg, 95% CI: −10 to −1), while 21 participants reduced their diabetes medication dose with two participants discontinuing all diabetes medication. These findings demonstrate that people with T2D receiving LCD education and resources through the Defeat Diabetes app for 3 months improved their glycaemic profile and SBP despite decreased overall medication usage in almost one third of the study sample prescribed medication at baseline.